(untitled) (International journal of artificial intelligence, 2026)
The article examines such theoretical issues as artistic psychologism in the depiction of the human psyche in works of art, the history of the emergence of the psychological approach and the psychological school as a scientific direction, the psychological type of the creator and the creative process, artistic psychological images. In the story "People of War" by Nazar Eshonkul, a psychological portrait, the inner and outer appearance of the heroes, their speech, individual mental states, betrayal The author's poetic skill and stylistic originality are analyzed in light of his effective use of artistic details such as self-examination, internal conflict, literary hallucination, and dream .